Накануне мировой субмаринной метаногидратодобычи - Шнюков, Е.Ф.; Гожик, П.Ф.; Краюшкин, В.А.; Клочко, В.П. (Видавничий дім "Академперіодика" НАН України, 2007)
In the World Ocean's bottom sedimentary sequence, the submarine gas hydrate reserves are fabulously tremendous. Best of all, they have been ready for commercial production on the Atlantic continental margin of the United States and in the Nankai Trough near the Honshu Island, the Japan, whereas the natural gas is already recovered from the gas-hydrate-bearing sequence in the Norwegian Sea.